The Roles of Natural Alkaloids and Polyphenols in Lipid Metabolism: Therapeutic Implications and Potential Targets in Metabolic Diseases - Ma, Zeqiang; Wang, Shengnan; Miao, Weiwei; Zhang, Zhiwang; Yu, Lin; Liu, Siqi; Luo, Zupeng; Liang, Huanjie; Yu, Jingsu; Huang, Tengda; Li, Mingming; Gao, Jiayi; et al. (Current Medicinal Chemistry, 2023)
The prevalence of obesity and its associated diseases has increased dramatically, and they are major threats to human health worldwide. A variety of approaches, such as physical training and drug therapy, can be used to reduce weight and reverse associated diseases; however, the efficacy and the prognosis are often unsatisfactory. It has been reported that natural food-based small molecules can prevent obesity and its associated diseases. Among them, alkaloids and polyphenols have been demonstrated to regulate lipid metabolism by enhancing energy metabolism, promoting lipid phagocytosis, inhibiting adipocyte proliferation and differentiation, and enhancing the intestinal microbial community to alleviate obesity. This review summarizes the regulatory mechanisms and metabolic pathways of these natural small molecules and reveals that the binding targets of most of these molecules are still undefined, which limits the study of their regulatory mechanisms and prevents their further application. In this review, we describe the use of Discovery Studio for the reverse docking of related small molecules and provide new insights for target protein prediction, scaffold hopping, and mechanistic studies in the future. These studies will provide a theoretical basis for the modernization of anti-obesity drugs and promote the discovery of novel drugs.
Keywords: Obesity